Ultimate capacity of a segmental grey cast iron tunnel lining ring subjected to large deformations. (April 2017) - Afshan, S.; Yu, J.B.Y.; Standing, J.R.; Vollum, R.L.; Potts, D.M.
Abstract: Understanding the behaviour of existing tunnels subjected to in-service deformations, as a result of the construction of underground works (e.g. new tunnels) in their proximity, is of importance in order to safeguard infrastructure within the urban environment. The associated deformations that take place during tunnelling have to be carefully assessed and their impact on the existing tunnels needs to be considered. A half-scale segmental grey cast iron (GCI) tunnel lining ring was tested as part of an extensive research project investigating the impact of new tunnel excavations on existing tunnels conducted at Imperial College London. A sophisticated experimental arrangement was developed to deform the ring in a variety of modes under combined displacement and load control. This paper reports on experiments carried out to assess its structural response when subjected to large deformations. The tests reported are the first to be conducted on a realistic scale model under carefully controlled conditions, and provide valuable insight into the behaviour of a GCI segmental ring during distortions commonly observed in reality. Details of the experiments, including the adopted test set-up and the instrumentation employed, are presented. The measured bending moments around the ring, as a result of the applied deformations, are determined and compared with those predicted using the well-known equations given by Morgan (1961) and Muir Wood (1975), often used in industry, as well as those obtained assuming an elastic continuous ring.